Optimized bi-material layouts for energy dissipating composites under finite deformations. (1st June 2020) - Alberdi, Ryan; Khandelwal, Kapil
Abstract: This study investigates the use of topology optimization as a method for discovering novel layouts of material phases which enhance the energy dissipation capacity of bi-material polymeric composites. Motivated by the experimental and numerical results in Wang et al. (2011), a multi-material topology optimization approach is developed to design composites consisting of a hard glassy polymer phase and soft elastomer phase undergoing large deformations. Computational homogenization is carried out to simulate the composite behavior and the energy dissipated as plastic work in the glassy polymer phase is maximized. The topology optimization examples investigated herein show the ability of the developed framework to exploit the physical phenomena reported in Wang et al. (2011) to improve energy dissipation capacity. Different deformation modes are considered and the influence of symmetry, phase volume fraction, and material rate effects on optimized composites is investigated. Additionally, the design of composites with a soft phase providing energy dissipation capacity and hard phase providing stiffness is carried out to show how vastly different phenomena are exploited to dissipate energy in optimized composites of this type.